Domestic work and Good Living: A challenge for advertising narratives - Camusso, Mariángeles (2017)
The notions of stereotype, sexism and symbolic violence are not only regular categories in academic work analyzing advertisements and campaigns, but also, thanks to the militant efforts of many organizations and educational initiatives, have begun to be part of media doxy and everyday language. This paper seeks to present the observations carried out throughout almost ten years of existence of the Advertising Observatory on Sexism of the UAI's Bachelor's degree in Advertising, bearing in mind the regularities and transformations of housework depiction.